The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/pr10010010
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic Amine Content in Retailed Cheese Varieties Produced with Commercial Bacterial or Mold Cultures

Abstract: Biogenic amines (BAs) are considered a potential microbiological toxicological hazard in aged cheese. Risk mitigation strategies include good hygiene practice measures, thermal treatment of milk and the use of competitive dairy cultures. The aim of this study was to evaluate the amount of BAs—tryptamine, β-phenylethylamine, putrescine, cadaverine, histamine, tyramine, spermidine and spermine—in the core and rind of cheeses ripened by bacteria (n = 61) and by mold cultures (n = 8). The microbial communities wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 31 publications
1
16
0
1
Order By: Relevance
“…A total of 84 isolates of presumptive Y. enterocolitica were selected for matrix-assisted laser desorption/ionization time of flight mass spectrometry identification (MALDI-TOF MS, Bruker Daltonik, Bremen, Germany), with detailed description provided in a recent study [18].…”
Section: Identification Of Isolates By Maldi-tof Ms and Real Time Pcrmentioning
confidence: 99%
“…A total of 84 isolates of presumptive Y. enterocolitica were selected for matrix-assisted laser desorption/ionization time of flight mass spectrometry identification (MALDI-TOF MS, Bruker Daltonik, Bremen, Germany), with detailed description provided in a recent study [18].…”
Section: Identification Of Isolates By Maldi-tof Ms and Real Time Pcrmentioning
confidence: 99%
“…Various solvents were used for the extraction of Bas, taking into consideration the characteristics of the analyzed samples. Solutions of 0.2 M perchloric acid was previously proposed for fish products [ 26 ], 0.4 M and 0.6 M for cheeses [ 5 , 27 ]. Hydrochloric acid 0.1 M was also applied before for cheeses [ 20 ], 5% trichloroacetic acid for meat [ 28 ], and 10% TCA for various foods [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a study performed in Austria, this amine was detected mainly in hard cheeses with the maximum concentration of 486.4 mg/kg in Cantal, the French raw milk cheese [ 5 ]. In other studies, high concentrations of tyramine were found in mold-ripened cheese (762.75 mg/kg) and semi hard cheese (767.03 mg/kg) [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Protective cultures do not alter the sensory properties of cheese, but, rather, the cheese safety by suppressing the pathogenic microbiota. In this sense, their antimicrobial properties in cheese production are directed to toxigenic molds, amine-producing microbiota, or foodborne pathogens, such as Listeria monocytogenes [203,215,222].…”
Section: Selection Of Indigenous Lab For Dairy Culturesmentioning
confidence: 99%